New round spore mutations in Neurospora crassa accompanying changes in a duplication closely linked to the R locus - D. J. Jacobson (Fungal Genetics Reports, 1992)
Various genotypes can result in round ascospores in N. crassa (Mitchell 1966 Neurospora Newsl. 10:6; Barry et al. 1972 Neurospora Newsl. 19:17). I have observed that round ascospores can also originate in crosses where one parent is the apparent breakdown of a partial diploid heterozygous at the heterokaryon incompatibility locus het-5. The breakdown may remove one of the duplicated chromosome segments carrying a het-5 allele and possibly extend past the duplication and affect the nearby Round spore locus (R).